A systematic review of diagnostic, prognostic, and risk blood and urine biomarkers of transplant-associated thrombotic microangiopathy - Schoettler, Michelle L.; Bhatt, Harshil; Vasu, Sumithira (Frontiers in Immunology, 2023)
Transplant associated thrombotic microangiopathy (TA-TMA) is an increasingly recognized complication of allogeneic and autologous hematopoietic cellular therapy (HCT) associated with significant morbidity and mortality. While the central drivers of disease are thought to be endothelial damage and complement activation there are no identified specific diagnostic biomarkers. TA-TMA is typically diagnosed using criteria comprised of non-specific clinical and laboratory features. Some patients will have a self-remitting course, but more than half progress to develop multi-organ dysfunction or death, making prognostic biomarkers critical. We conducted a systematic review to summarize diagnostic, early risk, and prognostic biomarkers of TA-TMA. We screened the titles and abstracts of 1524 citations. After screening out duplications, we read the abstracts of 979 papers, and fully reviewed 132 full text publications. Thirty-two publications fulfilled inclusion criteria of > 5 patients with TA-TMA and a reported measure of association with diagnosis, prognosis, or risk of later development of disease. Fourteen studies (45%) were enriched with adults, 12 (39%) with children <18 years old, 3 included both children and adults and 2 did not report age. There were 53 biomarker or biomarker signature entries, and a total of 27 unique biomarkers. Only 4 biomarkers reported sensitivity and specificity. The single biomarker with the most robust data was sC5b-9 which conferred diagnostic, prognostic and risk implications. Studies of combinations of biomarkers were rare. No meta-analyses were performed because of significant heterogeneity between studies. Limitations of studies included small sample size, study designs with high risk of bias (i.e. case control), timing of sample collection, and selection of controls. Further, only 2 (6%) of studies included a training and validation cohort. Cut off points are needed to stratify groups as most biomarkers do not have normal values, or normal values cannot be assumed in the HCT setting. In the future, multi-institutional, collaborative efforts are needed to perform rigorously designed, prospective, studies with serially enrolled patients, samples collected at the time of TA-TMA diagnosis, careful selection of controls, and validation of selected biomarkers and cut points in a separate cohort.